Satisfaction of Dairy Farmers from Para-veterinary Services: An Exploratory Study - Kumar, Vikash; Meena, HR (Indian Journal of Extension Education, 2025)
With an acute shortage of manpower delivering animal health service in India, a concern for efficient delivery of minor veterinary services have gained popularity amongÂ stakeholders. The present study aims to measure the satisfaction of farmers towards paraveterinary services in Mathura, Hisar, Jaipur, and Ahmadnagar districts of states namely,Uttar Pradesh, Haryana, Rajasthan, and Maharashtra respectively. A total of 160 dairyÂ farmers were studied under the random sampling method of investigation. SatisfactionÂ towards tasks under minor veterinary services was compared and ranked using weighted mean scores among different states. From Pearsonâ€™s product-moment correlation, amongÂ various socio-economic variables, education of farmers was found to have a negative relationship with the level of satisfaction of farmers towards para-veterinary services, while the distance from veterinary hospital/ dispensary was found positively correlated. AgeÂ and landholding were found non-significantly associated with satisfaction of farmers towards minor- veterinary services. It was found that 44.38 per cent of respondents were moderatelyÂ satisfied, followed by 35.62 per cent respondents revealing a high level of satisfaction towards para-veterinary services.